In-vitro antimicrobial activity of Jatropha variegata Vahl. (Euphorbiaceae) against some pathogenic microbes isolated from clinical samples in Ibb City, Yemen - Abeer Esmail; Hassan Alkhshar; Esam Aqlan; Bashar Atef; Turki Abdullah; Othman Al-parah; Bakil Alashmali; Radwan Almshrqyi; Montaser Ahmed; Mouath Qasim; Najmaldyn Alnsyry (Scientific Reports)
Abstract This study aimed to evaluate the in-vitro antimicrobial activity of Jatropha variegata against pathogenic microbes isolated from clinical samples in Ibb City. Fresh samples of leaves and stems were collected from various locations in Ibb, Yemen. The well diffusion method was employed to evaluate the antimicrobial activity of the plant extracts against specific bacteria and Candida. The phytochemical evaluation of Jatropha variegata leaves and stems revealed that tannins and sterols were most concentrated in the ethanolic extract. The leaves of Jatropha variegata exhibited notable antibacterial activity, producing inhibition zones of 18 mm against Staphylococcus aureus, and 15 mm against both Escherichia coli and Pseudomonas aeruginosa. In contrast, Enterobacter spp., Klebsiella spp., and Proteus spp. displayed resistance to the leaf extract. The minimum inhibitory concentration (MIC) of the stem extract was 100 mg/mL for Staphylococcus aureus, Escherichia coli, Salmonella spp., and Candida spp. For the leaf extract, the MIC was higher, “400 and 500 mg/mL” for Staphylococcus aureus and Pseudomonas aeruginosa, respectively, while remaining 100 mg/mL for Escherichia coli, Salmonella spp., and Candida spp. The minimum bactericidal concentration (MBC) of the stem extract was 500 mg/mL against Staphylococcus aureus and 100 mg/mL against Salmonella spp. Notably, the combined leaf and stem extracts demonstrated enhanced antimicrobial efficacy, evidenced by larger inhibition zones and improved MIC and MBC profiles, highlighting a potential synergistic effect.